Controlling endemic Neospora caninum-related abortions in a dairy herd from Argentina - Lagomarsino, Horacio (2019)
After diagnosis of endemic abortions due to neosporosis in a commercial dairy farm, routes of Neospora caninum-transmission were evaluated in order to choose the best strategy for reducing its seroprevalence and related abortions. Fifty two dam-calf pairs were bled at parturition. Additionally, 22 female calves were also sampled at regular 3 month intervals until 18–22 months. N. caninum specific antibodies were assayed by IFAT. Serum samples were tested at a dilution 1:25 for calves before colostrum intake and heifers before mating and 1:100 for multiparous cows. Only serum samples from IFAT seropositive cattle involved in the evaluation of the routes of transmission were assessed by a commercial IgG avidity ELISA. Seropositive cows or heifers were artificially inseminated with semen from Hereford bulls. The progenies from these female animals were sent to a feed lot to produce meat. Different generalized linear models (GLM) were used to study the relationship between abortion, age category, and serostatus. Seropositive heifers were more likely to have a record of abortion (OR 2.7; 95% CI 1.6–4.7). Vertical transmission frequency was 55.5% (5 seropositive calves/9 seropositive cows). Horizontal transmission was 22.7% (5 female calves seroconverted at least one time/22 females calves sampled during 24 months) and these 5 female calves had low avidity. In heifers, both seroprevalence and abortion rates decreased from 22.1 and 8.4% of 475 in 2009 to 6.1 and 4.3% of 578 in 2015, respectively (p < 0.01). Over 5 years, N. caninum-seroprevalence and the related abortions in heifers decreased after the control strategy was assessed.